Internal Reporting Systems Supporting Managerial Accountability (gjstudies, 2019)
This research introduces a novel, cross-disciplinary framework for internal reporting systems that fundamentally re-conceptualizes managerial accountability as a dynamic, multiagent feedback process rather than a static compliance mechanism. Departing from traditional accounting and information systems literature, which often treats reporting as aunidirectional flow of sanitized financial data, we propose a bio-inspired, stigmergic model.This model leverages principles from swarm intelligence and complex adaptive systems observed in social insects, where accountability emerges from decentralized interactions andenvironmental markers left by managerial actions. Our methodology employs an agentbased simulation to model an organization as a heterogeneous network of managerial agentswith varying propensities for transparency, cooperation, and self-justification. The core innovation of the proposed Internal Stigmergic Accountability Reporting (ISAR) system isits use of digital pheromone trails—persistent, decaying data signatures attached to decisions, resource allocations, and outcomes. These trails allow for the non-linear, emergentreconstruction of causal accountability pathways, enabling the system to highlight not justwhat happened, but the often-opaque chain of influences and rationales behind outcomes.The simulation results, analyzed using network entropy and coherence metrics, demonstratethat ISAR systems significantly increase the detectability of diffused accountability andrationalization cascades compared to traditional hierarchical reporting. Furthermore, thesystem uniquely fosters a form of generative accountability, where the visibility of digitalpheromone trails influences future managerial behavior in a positive feedback loop, promoting more deliberate and justifiable decision-making. This research makes an originalcontribution by bridging computational theory with organizational behavior, offering a toolnot for surveillance, but for cultivating a richer, more transparent epistemic environmentwhere accountability is an integrated byproduct of organizational communication, therebysupporting more resilient and ethically aware management structures.